Challenges in the Direct Determination of 17Oexcess in Microliter Amount of Water Extracted From Speleothem Fluid Inclusions - Affolter, Stéphane; Leuenberger, Markus C. (Frontiers in Earth Science, 2021)
Water isotopes are powerful proxies able to deliver valuable information about past climate conditions at the precipitation site, along the path of the moisture or at its source. We use a recently developed microliter sampling technique associated to continuous-flow laser spectroscopy in order to investigate its potential for direct determination of 17Oexcess on microliter amount of water released from speleothem crushing. Results from Milandre Cave stalagmite (Switzerland) suggest that 17Oexcess from speleothem fluid inclusion water could likely be used as a paleoclimate proxy and to resolve past hydroclimatic changes mainly depending on (i) the technical capability to produce precise and accurate direct measurements and (ii) our understanding of which factors influence the 17Oexcess proxy in speleothem fluid inclusion water. With our setup, the main challenge regarding 17Oexcess measurements is the very low amount of water released by the crushing of speleothem samples, which also lead to the difficulty of producing sample replications. The precision achieved based on duplicate measurements is ~30 per meg, which is currently a value too high to retrieve robust paleoclimate information. We suggest sample replications and further improvement of the presented method through the increase of the signal to noise ratio and correction for isotope composition – mixing ratio dependence to reach the required precision of 10 per meg or less.